Association between the 400-m walk test and sensor-based daily physical activity in frail and sarcopenic older adults - Rogler, Jana; Krumpoch, Sebastian; Freiberger, Ellen; Lindemann, Ulrich; Kob, Robert (European Geriatric Medicine, 2025)
Aim: Our objective was to examine the association between the time and number of stops during the 400-meter walk test (400MWT) and average daily steps and walking cadence in a German cohort of frail and sarcopenic community-dwelling older adults at first observation (FO) and individual last observation (LO) after at least 11 months. Findings: Stops during the 400MWT led to a longer time. Time in the 400MWT was significantly associated with average daily steps and walking cadence at FO and LO (24.5 ± 8.5 months). Stops alone were not associated with average daily steps and walking cadence. Message: Gait speed under laboratory conditions can be used to estimate daily physical activity, represented by average daily steps and walking cadence, in frail and sarcopenic older adults.
CRIS-Team Scopus Importer:2025-07-04
Keywords: 400-m walk test; Daily activity; Frailty; Older adults; Sarcopenia